Two-Phase Flow Metering Using A Large Coriolis Mass Flow Meter Applied To Ship Fuel Bunkering - Gregory, D; West, M; Paton, R; Casimir, R; Boo, S; Low, Y; Henry, M; Tombs, M; Duta, M; Zhou, F; Zamora, M; Mercado, R; et al. (2008)
With rising oil prices, there is growing interest in more accurate measurement during transfers of marine fuel oil, whether for the purposes of environmental monitoring or for validating custody transfer. Air entrainment is a common problem in marine fuel transfer (bunkering) operations, which can induce measurement errors in many metering technologies. The latest generation of Coriolis mass flow meters is able to operate in both single- and two-phase (oil-air) flow conditions. Witnessed trials have taken place at the National standards laboratories at TUV NEL Ltd in the UK using a large (200mm diameter) Coriolis flowmeter. These independent facilities have a unique combination of multiphase and heavy oil flow research capabilities. The accuracies of the mass flow and density measurements were assessed for steady single-phase and two-phase flow on high and low viscosity oils. Meter accuracy was further assessed over a series of simulated bunkering operations, in which the meter started and finished empty of oil, with periods of both single and two-phase operation. Further trials of a metering skid are currently being carried on a bunkering vessel in Singapore.